Terytorialne więzi sieciowe - studium przypadku Związku Sześciu Miast Łużyckich - Przybyła, Zbigniew (Territorial Net Connections - Case Study of the association of the Six Cities in Łużyce, 2008)
The most essential component of the exterior of interterritorial cooperation in the European Union's states structure are the partnership contacts which are formed on the level of all types of spatial-administrative units. The most often encountered relation of this kind of associations is cooperating of the partner-cities (twin-cities). It can be represented as the form of two-sided (bilateral) or net connections. The characteristic manifestation of the net cooperation is an example of the Association of the Six Cities in Łużyce and its historical aspects and now - the subject of this article.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 10, s. 105-114